Gesp: A computer program for modelling genetic effective population size, inbreeding and divergence in substructured populations. (21st April 2017) - Olsson, Fredrik; Laikre, Linda; Hössjer, Ola; Ryman, Nils
Abstract: The genetically effective population size ( N e ) is of key importance for quantifying rates of inbreeding and genetic drift and is often used in conservation management to set targets for genetic viability. The concept was developed for single, isolated populations and the mathematical means for analysing the expected N e in complex, subdivided populations have previously not been available. We recently developed such analytical theory and central parts of that work have now been incorporated into a freely available software tool presented here.gesp (Genetic Effective population size, inbreeding and divergence in Substructured Populations) is R‐based and designed to model short‐ and long‐term patterns of genetic differentiation and effective population size of subdivided populations. The algorithms performed bygesp allow exact computation of global and local inbreeding and eigenvalue effective population size, predictions of genetic divergence among populations ( G ST ) as well as departures from random mating ( F IS, F IT ) while varying (i) subpopulation census and effective size, separately or including trend of the global population size, (ii) rate and direction of migration between all pairs of subpopulations, (iii) degree of relatedness and divergence among subpopulations, (iv) ploidy (haploid or diploid) and (v) degree of selfing. Here, we describegesp and exemplify its use in conservation genetics modelling.